Burden, satisfaction caregiving, and family relations in informal caregivers of older adults - Marinho, Jéssica da Silva; Batista, Ilaise Brilhante; Nobre, Rute Alessandra da Silva; Guimarães, Maria Sortênia Alves; Santos-Orlandi, Ariene Angelini dos; Brito, Tábatta Renata Pereira; Pagotto, Valéria; Saidel, Maria Giovana Borges; Fusco, Suzimar de Fátima Benato; Maia, Flavia de Oliveira Motta; Corona, Ligiana Pires; Nunes, Daniella Pires (Frontiers in Medicine, 2022)
Introduction: Family caregivers of older persons devote much of their time and energy to caring for another person. This exposure may burden caregivers and compromise their health and quality of life. Objective: To investigate the relationship between burden, sociodemographic, caregiving, and health characteristics of informal caregivers of dependent older adults. Method: Cross-sectional and analytical study carried out in Palmas, Tocantins, Brazil, with 52 informal caregivers of older persons who need full-time help for basic living activities. Caregivers’ burden was assessed by Zarit Burden Interview (ZBI). Data were analysed using a T-test, Pearson’s correlation, and Multiple Linear Regression. Results: The ZBI mean score of caregivers was 26.3 points (SD=14.6; min=0; max=68). Burden scores were higher among caregivers who did not receive help from other people in care (p=0.016), reported family dysfunction (p=0.001), and had depression symptoms (p=0.007). A correlation was found between the scores of burdens and satisfaction with care (r=0.76; p<0.001) and perceived material support (r=-0.30; p=0.40). Satisfaction with care (β: 0.61; p<0.001) and family dysfunction (β: 8.07; p=0.033) were significantly associated with the burden score. Conclusion: Caregivers with dysfunctional families and satisfaction with the care presented the highest-burden scores. The findings reveal the need for strategies to facilitate mediation and reduce caregiver burden by strengthening the family network support or providing professional assistance.